2018
DOI: 10.1111/dar.12847
|View full text |Cite
|
Sign up to set email alerts
|

Methods for calculation of per capita alcohol consumption in a Muslim majority country with a very low drinking level: Findings from the 2011 Iranian mental health survey

Abstract: Unlike in surveys of non-Muslim countries, frequency of drinking from recent recall (last week) was much lower than from recall of usual drinking in the last year. We conclude that 0.108 L (SE = 0.03) is the best survey-based estimate of age 15+ per capita consumption, which translates to about 5 750 000 L of national consumption per year in Iran. However, this method is still likely to under-estimate per capita consumption due to evidence of under-reporting in the survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
1
13
1
Order By: Relevance
“…Only one study from Iran estimated the 15+ year‐old persons’ per capita alcohol consumption (APC) as 0.1 l (standard error = 0.03; males: 0.2; females: 0.01) based on a national household survey [20]. No other study from other countries in the region was found.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study from Iran estimated the 15+ year‐old persons’ per capita alcohol consumption (APC) as 0.1 l (standard error = 0.03; males: 0.2; females: 0.01) based on a national household survey [20]. No other study from other countries in the region was found.…”
Section: Resultsmentioning
confidence: 99%
“…In the commercial context, the process of obtaining alcoholfree propolis extract is notably relevant. In countries, where most of the population is Muslim, less consumption of alcohol occurs, since it is forbidden to drink alcoholic beverages in the Islamic religion, requiring control in the production and import of alcohol in these countries (Al-ansari et al, 2015(Al-ansari et al, , 2019Amin-Esmaeili et al, 2018). In addition to this group, abstainers and children are others who would be restricted from consuming alcoholic extracts.…”
Section: Experimental Validationmentioning
confidence: 99%
“…After the Islamic Revolution in Iran, the consumption of alcoholic beverages was declared illegal, making it difficult to estimate the burden of alcohol-related disease (Amin-Esmaeili et al, 2018). Therefore, very accurate statistics on the extent of alcohol consumption are not available for Iran (Amin-Esmaeili et al, 2018;Samadi et al, 2017). Despite such severe restrictions, the mean age of onset of alcohol consumption is 16.7 years, and the main alcoholic beverage is a homemade drink (Samadi et al, 2017).…”
Section: Dear Editormentioning
confidence: 99%
“…Also, the stigma associated with alcohol consumption poses challenges for implementing alcohol screening in primary health care (Al-Ansari et al, 2019). Considering the conservative context of Iranian society, most existing studies on alcohol use are based on self-reporting by participants who might be prone to underreporting (Amin-Esmaeili et al, 2018;Rostami & Rezaeian, 2019). These may indicate that the national burden of disease due to alcohol is underestimated.…”
Section: Dear Editormentioning
confidence: 99%